Social Context, Institutional Capacity, and Police Services: A Local Public Economies Perspective. - Leon‐Moreta, Agustin (Public Administration Review)
This article examines levels of policing services, focusing on an assessment of resources and their measurement for municipalities. Two measures of policing levels assess the reliability of the findings across alternative measurements. Social and institutional characteristics are explored to evaluate alternative explanations in policing efforts. The article presents four decades of census data for municipalities in metropolitan areas. The central finding is that unequal levels of policing are prevalent across American municipalities. An additional finding is that social and institutional contexts affect policing, based on a pooled time‐series analysis of municipal governments. Although its main contribution is to local public economies research, the research also integrates the social and institutional literatures to identify factors in the allocation of resources to policing.